1999
DOI: 10.1021/om980786y
|View full text |Cite
|
Sign up to set email alerts
|

New Niobocene Alkyne Complexes:  Synthesis and Characterization of Neutral and Cationic Niobium Complexes with Functionalized Alkynes. X-ray Crystal Structure of [Nb(η5-C5H4SiMe3)2(Cl)(η2(C,C)-R1C⋮CR2)] (R1= C⋮CPh, R2= Ph (2b); R1= CH2CHC(CH3)2, R2= Ph (3b))

Abstract: The diyne-containing niobocene complexes Nb(η5-C5H4SiMe3)2Cl(η2(C,C)-R1C⋮CR2) (R1 = C⋮CSiMe3, R2 = SiMe3 (2a); R1 = C⋮CPh, R2 = Ph (2b); R1 = CH2CH2C⋮CH, R2 = H (2c)) were prepared by the reaction of Nb(η5-C5H4SiMe3)2Cl (1) with the diyne reagents, R−C⋮C−C⋮C−R (R = SiMe3 or Ph) and 1,5-hexadiyne. The enyne-containing niobocene complexes Nb(η5-C5H4SiMe3)2Cl(η2(C,C)-R1C⋮CR2) (R1 = CH2CHCH2, R2 = Ph (3a); R1 = CH2CHC(CH3)2, R2 = Ph (3b); R1 = CH2C(CH3)CH2, R2 = Ph (3c); R1 = C(CH3)CH2, R2 = H (3d)) were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Otero and Royo also showed that, in the case of (Cp Si ) 2 NbCl 2 ( 27 ), the use of 1 equiv of reducing agent afforded the isolable Nb III monochloride (Cp Si ) 2 NbCl ( 28 ), as shown in Scheme . While the addition of 1 equiv of alkyne generated the desired alkyne complex (Cp Si ) 2 M­(RCCR)Cl ( 29 ), treating 28 with 1 equiv of a diyne, such as 1,4-diphenylbuta-1,3-diyne, afforded the related complex Cp′ 2 M­(RCCCCR)­Cl ( 30 ) …”
Section: Synthesis Of Tantalum and Niobium Alkyne Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…Otero and Royo also showed that, in the case of (Cp Si ) 2 NbCl 2 ( 27 ), the use of 1 equiv of reducing agent afforded the isolable Nb III monochloride (Cp Si ) 2 NbCl ( 28 ), as shown in Scheme . While the addition of 1 equiv of alkyne generated the desired alkyne complex (Cp Si ) 2 M­(RCCR)Cl ( 29 ), treating 28 with 1 equiv of a diyne, such as 1,4-diphenylbuta-1,3-diyne, afforded the related complex Cp′ 2 M­(RCCCCR)­Cl ( 30 ) …”
Section: Synthesis Of Tantalum and Niobium Alkyne Complexesmentioning
confidence: 99%
“…59 While the addition of 1 equiv of alkyne generated the desired alkyne complex (Cp Si ) 2 M(RCCR)Cl (29), treating 28 with 1 equiv of a diyne, such as 1,4-diphenylbuta-1,3-diyne, afforded the related complex Cp′ 2 M(RCCCCR)Cl (30). 60 Although the majority of work in this field has focused on cyclopentadienyl-containing systems such as the ones discussed above, alkyne moieties have been installed via a similar reduction protocol in Ta and Nb complexes featuring a variety of ancillary ligand sets. For example, McConville and co-workers 30 investigated the synthesis of Ta alkyne complexes featuring a pyridine-diamido pincer ligand, BDPP, as shown in Scheme 9.…”
Section: Alkyne Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…76 Syntheses, characterisation and some reactions have been reported for [NbCl(Z 2 (C,C)-R 1 CCR 2 )(Z 5 -C 5 H 4 SiMe 3 ) 2 ] (R 1 CCSiMe 3 , R 2 SiMe 3 ; R 1 CCPh, R 2 Ph; R 1 CH 2 CH 2 CCH, R 2 H). 77 The reactions of [NbCl 4 (Z 5 -C 5 H 4 SiMe 3 )] and [TaCl 2 (Me) 2 Cp*] with NHRSiMe 3 and CNR have been studied for a range of R groups. 78 Syntheses of the N-alkoxy-b-ketoiminate complexes [Nb(Z 5 -C 5 H 4 R){CH 3 C(O)-CHC(NCH 2 CHR H O)CH 3 }Cl 2 ] (R H, Me; R H H, Me), have been described.…”
Section: Niobium and Tantalummentioning
confidence: 99%
“…From analysis of the published data, it follows that Zn, 39 Mg, Al, [40][41][42][43] and Na/Hg amalgam [44][45][46][47][48][49] are the most popular reducing agents suitable for efficient generation of low-valent niobium and tantalum in the presence of alkyne molecules. Oshima and co-workers reported for the rst time that the reaction of nonfunctionalized disubstituted acetylenes with low-valent niobium, generated by reduction of NbC1 5 with NaAlH 4 , results in the selective formation of monodeuterated Z-olens.…”
Section: Introductionmentioning
confidence: 99%